Damping characteristics of PVA fiber-reinforced cementitious composite containing high-volume fly ash under frequency-temperature coupling effects. (April 2021) - Long, Wu-Jian; Li, Hao-Dao; Mei, Liu; Li, Weiwen; Xing, Feng; Khayat, Kamal H.
Abstract: The service life of concrete structures is often threatened by unfavorable dynamic loads. Optimizing the material damping can improve the vibration damping of the structure. In this study, a polyvinyl alcohol fiber-reinforced high-volume fly ash (PVA-HVFA) cementitious composite was developed with high damping characteristics and moderate mechanical properties. The coupling effects of frequency and temperature on the damping were further clarified. Experiments combined with MIP and SEM tests were performed to analyze the pore structure distribution, fiber–matrix morphology, and enhanced damping mechanism. The results showed that the large amount of FA adversely affected strengths of the PVA-HVFA but significantly improved the damping and energy dissipation capacity. Meanwhile, the PVA fibers enhanced both strengths and damping characteristics. Vibration damping and energy dissipation were hypothesized to be affected by the matrix, fibers, and fiber–matrix interface. PVA-HVFA is expected to be applicable to beam–column plastic hinges and other vibrational damping fields. Highlights: Novel PVA fiber-reinforced composite with superior damping property is developed. Damping performance characterized by fiber content and fly ash substitution rate. Coupling effects of excitation frequency and temperature are clarified. Pore structure and distribution significantly affect the damping of PVA-HVFA. Damping mechanism explained in terms of matrix, fibers, and fiber–matrix interface.